The antibacterial effect of β-pinene derived from Citrus aurantifolia peel against oral Streptococcus mutans ATCC 25175 - Julaeha, Euis; Herlina, Tati; Nurzaman, Mohamad; Mayanti, Tri; Kurnia, Dikdik; Sari, Elizabeth Fitriana (Padjadjaran Journal of Dentistry, 2021)
Introduction: Streptococcus mutans has been known to play a major role in dental caries development. This tooth decay is the most common oral disease affecting people in the world. Hence, discovering the new herbal antibacterial agent seems to become more promising yet challenging. One of natural antibacterial source is the peel of Citrus aurantifolia, as it may contain antibacterial active compounds against pathogenic oral microbes. This study was aimed to isolate antibacterial compound from essential oil of Citrus aurantifolia and to analyse its antibacterial activity against oral Streptococcus mutans ATCC 25175. Methods: Type of research was laboratory experimental. The essential oil was isolated from peel of Citrus aurantifolia by hydro-distillation technique and further isolation of antibacterial compounds was conducted by combination column chromatography using organic solvent, and the structure was determined by UV-Vis, infrared (IR), 1D NMR of 1H-, 13C-NMR and DEPT 135° in CDCl3 spectrometers methods. The antibacterial activity was tested against Streptococcus mutans ATCC 25175 using the Kirby-Bauer method. Results: 0.75% yield was obtained from the essential oil of peel Citrus aurantifolia and after purification, an antibacterial compound was identified as β-pinene with the molecular formula C10H16. Furthermore, the β-pinene from peel of Citrus aurantifolia exerted inhibition growth against Streptococcus mutans at concentration of 2000, 1000, and 500 ppm by showing respectively, inhibition values of 13.0, 11.9, and 11.6 mm on paper disk. Conclusion: In the present study, the essential oil of Citrus aurantifolia peel is proven to contain prospective antibacterial compound (β-pinene) that potentially can be used as natural antibacterial alternative choice to manage oral disease associated with Streptococcus mutans infection.